Globalisasi, Inflasi Dan Tradeoff Inflasi – Ouput Perspektif Makro Ekonomi Indonesia - Sari Narulita; Vetri Yanti Zainal (Universitas Hamzanwadi, 2022)
This paper aims to analyze the relationship between globalization and inflation from Indonesian macroeconomic perspective. This study uses autoregression (VAR) approach that relates the effects of globalization to inflation in Indonesia. With limited time and data, the measurement of inflation in this study follows a standard approach that uses the log of the average annual change in the log of the GDP deflator. . As an alternative measure, we will also consider the annual log average change in the log of the consumer price index.The effects of globalization are measured through open finance and trade. Higher trade and financial openness; i) reduce the central bank's inflation bias, resulting in lower average inflation, and ii) are associated with a larger inflation-output tradeoff. The test result using Vector autoregression (VAR) shows that the positive relationship between globalization and inflation tends to have long-term balance